Whole Transcriptome Profiling of the Effects of Cadmium on the Liver of the Xiangxi Yellow Heifer - Wei, Yameng; Yi, Kangle; Shen, Caomeihui; Chen, Xue; Iqbal, Tariq; Cao, Maosheng; Chen, Tong; Luo, Yang; Li, Jianbo; Zhou, Xu; Li, Chunjin; Chen, Lu (Frontiers in Veterinary Science, 2022)
Cadmium (Cd) is a major heavy metal toxicant found in industrial zones. Humans and animals are exposed to it through their diet, which results in various physiological problems. In the current study, the toxic effects of Cd on the liver were investigated by whole-transcriptome sequencing (RNA-seq) of the livers of Xiangxi heifers fed a diet with excess Cd. We randomly divided six healthy heifers into two groups. The first group received a control diet, whereas the second group received Cd-exceeding diets for 100 days. After 100 days, the livers were collected. A total of 551 differentially expressed mRNAs, 24 differentially expressed miRNAs, and 169 differentially expressed lncRNAs were identified (p < 0.05, |log2FC| >1). Differentially expressed genes (DEGs) were analyzed by gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses. We found that under Cd exposure, DEGs were enriched in the adenosine 5'-monophosphate–activated protein kinase pathway, which is involved in autophagy regulation, and the peroxisome proliferator–activated receptor pathway, which is involved in lipid metabolism. In addition, the apolipoprotein A4 gene, which has anti-inflammatory and antioxidant effects, the anti-apoptotic gene ATPase H+/K+ transporting the nongastric alpha2 subunit, and the cholesterol metabolism–associated gene endothelial lipase gene were significantly downregulated. C–X–C motif chemokine ligand 3, cholesterol 7α-hydroxylase, and stearoyl-CoA desaturase, which are involved in the development of fatty liver, were significantly upregulated. These genes revealed the main effects of Cd on the liver of Xiangxi yellow heifers. The current study provides insightful information regarding the DEGs involved in autophagy regulation, apoptosis, lipid metabolism, anti-inflammation, and antioxidant enzyme activity. These may serve as useful biomarkers for predicting and treating Cd-related diseases in the future.